2006
DOI: 10.1109/lpt.2006.884751
|View full text |Cite
|
Sign up to set email alerts
|

Spectrally Resolved Approach for Modeling Short Pulse Amplification in Er$^{3+}$-Doped Fibers

Abstract: Abstract-We study pulse propagation in Er 3+ -doped fiber amplifiers (EDFA) within the framework of a spectrally resolved pulse rate-propagation equations model. Our model accounts for the effects of gain dispersion, gain saturation, waveguide and chromatic dispersion, and amplified spontaneous emission. This model allows us to approximate the effects of nonlinear resonant dispersion on short pulse amplification in doped fibers, without reverting to the generalized nonlinear Schroedinger equation. Numerical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
(26 reference statements)
1
4
0
Order By: Relevance
“…We also demonstrated that by tuning the pump power, the amount of spectral compression of a negative-chirp incident pulse can be controlled. Our results provide additional support to experimental measurements of broad-bandwidth amplified pulses, which extends the standard NLSE formalism and can, in principle, be compared directly with the pulse spectrogram [10]. Furthermore, the model allows the inclusion of a realistic gain spectrum for the Stark-splitted doped ions transitions using measured cross sections, therefore alleviating some of the restrictions imposed by analytical gain approximations [7].…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…We also demonstrated that by tuning the pump power, the amount of spectral compression of a negative-chirp incident pulse can be controlled. Our results provide additional support to experimental measurements of broad-bandwidth amplified pulses, which extends the standard NLSE formalism and can, in principle, be compared directly with the pulse spectrogram [10]. Furthermore, the model allows the inclusion of a realistic gain spectrum for the Stark-splitted doped ions transitions using measured cross sections, therefore alleviating some of the restrictions imposed by analytical gain approximations [7].…”
Section: Discussionsupporting
confidence: 57%
“…In the spectral range relevant to optical amplification, i.e., at nm (see inset), the dispersion is normal, and it monotonically increases from to ps km nm . Thus, gain-induced dispersion fluctuations are expected to have only small effect on an amplified pulse, in contrast to Er -doped fibers [10]. In what follows, we demonstrate the effects of various physical parameters on the spectral and temporal characteristics of a short amplified pulse.…”
Section: Examplesmentioning
confidence: 64%
See 2 more Smart Citations
“…[24][25][26][27][28] The rate equations describe the relations among the excited states of all the ions. The equations in this model include the pumping power absorption by Er, Yb, and Nd ions, forward and backward energy transfers, ASE, and scattering losses.…”
Section: Theoretical Modelmentioning
confidence: 99%